2021
DOI: 10.3390/app112311565
|View full text |Cite
|
Sign up to set email alerts
|

Causative Mechanisms of Childhood and Adolescent Obesity Leading to Adult Cardiometabolic Disease: A Literature Review

Abstract: The past few decades have shown a worrisome increase in the prevalence of obesity and its related illnesses. This increasing burden has a noteworthy impact on overall worldwide mortality and morbidity, with significant economic implications as well. The same trend is apparent regarding pediatric obesity. This is a particularly concerning aspect when considering the well-established link between cardiovascular disease and obesity, and the fact that childhood obesity frequently leads to adult obesity. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 314 publications
0
6
0
Order By: Relevance
“…The reason for the high VAI cut-off points and the lower sensitivity/specificity values determined in our study ​​may be due to the selection of the sample from the age group close to the pubertal period, as well as the differences in the distribution of adipose tissue in children with obesity. In a systematic review, it has been reported that the distribution of visceral adipose tissue in children and adolescents is associated with factors such as genetics, ethnicity, gender, age, developmental level, and puberty [ 29 ]. Therefore, these factors should be considered when evaluating predictors of cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the high VAI cut-off points and the lower sensitivity/specificity values determined in our study ​​may be due to the selection of the sample from the age group close to the pubertal period, as well as the differences in the distribution of adipose tissue in children with obesity. In a systematic review, it has been reported that the distribution of visceral adipose tissue in children and adolescents is associated with factors such as genetics, ethnicity, gender, age, developmental level, and puberty [ 29 ]. Therefore, these factors should be considered when evaluating predictors of cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…BMI does not always reflect an increase in fat mass at adiposity rebound or at early puberty [8 && ]. Thus, identifying each of the components of body composition is of great importance as excess adipose tissue is associated with a predisposition to health conditions in adulthood, such as cardiovascular disease and type 2 diabetes mellitus [9], also having an impact on quality of life, productivity, and life expectancy [10] ], these include anthropometric measurements, bioimpedance analysis (BIA), air displacement plethysmography (ADP), dual-energy X-ray absorptiometry (DXA), computed tomography (CT), and MRI, among others. However, each of these methods has advantages and disadvantages (Table 1).…”
Section: Diagnosis and Monitoring Of Excess Adiposity In Children And...mentioning
confidence: 99%
“…Currently, several anthropometric indicators have been described that provide information on the disposition of body fat at different body locations, namely, waist circumference [19], neck circumference [20], waist-to-height ratio (WHtR) [19,21], waist-to-hip ratio (WHR) [19], and A Body Shape Index [ABSI ¼ WC/(BMI 2/3 Â height 1/2 ) [22]. Other techniques offer specific information on the distribution of both VAT and SAT and measurements of localized fat deposits (Table 1) [9].…”
Section: Diagnosis and Monitoring Of Excess Adiposity In Children And...mentioning
confidence: 99%
See 2 more Smart Citations